(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
In the frame work of effective mass approximation, we have determined the donor binding energies of the most minimal donor states, \(1s\), \(2p_0\) and \(2p_±\), in zinc blende AlGaN/GaN Quantum dot in the impact of the magnetic field along the development(growth) directions. The calculations are performed utilizing variational method. The calculations are performed using variational method. As a function of the quantum dot radius and the applied magnetic field, the donor binding energies and diamagnetic susceptibilities are obtained. The oscillator quality of the potential transitions between the donor states is then figured by displaying them as the conditions of a two-level atom. Our outcomes demonstrate that (i) the donor binding energy is appreciable for smaller dot radii and magnetic field effect is predominant for larger dot radii, (ii) the diamagnetic susceptibility increases with applied magnetic field and is appreciable only for larger dot radii, (iii) The oscillator quality of the potential transitions between the donor states is not pronounced for smaller dot size radii and plays a significant role in larger dot radii.